ВОЗДУХОПРОНИЦАЕМОСТЬ ОДЕЖНЫХ ТКАНЕЙ ГЛАВНЫХ ПЕРЕПЛЕТЕНИЙ - Оразбаева, Р.И. (SCIENCE and SOCIETY, 2021)
As a criterion for assessing the structure of clothing fabrics, it is advisable to use air permeability. Therefore, a design technique was proposed on the basis of a given fabric air permeability. The following parameters of the fabric with a square structure of the main weaves were determined, such as the coefficient of air permeability, the percentage of unfilled and filled area of the fabric with fibrous material, the average number of the yarn, and the density of the fabric. An equation for the coefficient of air permeability of a square fabric is proposed, taking into account the sum of the numerator and denominator of fractions of the main weaves. Investigations of the parameters of the structure of the fabric of a square structure, depending on the weave, air permeability and surface density of the fabric, have been carried out. The increase in the number of threads in the report of the fabric with a square structure and air permeability is determined, which reduces the values of the average yarn number and the density of the fabric. Moreover, for air permeability, we have the invariability of the values of such parameters as the coefficient of air permeability, the percentage of uncovered area of the fabric and the relative density of the fabric.